Proses Penyelesaian Kasus Nusyuz Suami di Pengadilan Agama Stabat - Alfath Syuhada (Journal Smart Law, 2022)
Nusyuz is an act of disregarding one's rights and obligations in influencing the household ark This nusyuz can be done by the husband or wife, nusyuz can occur if the husband or wife leaves his obligations in the household as intended in article 1 of Law Number 1 of 1974 in saying that the purpose of marriage is to form a happy and eternal family. This thesis discusses how the process of resolving the husband's nusyuz case in the Stabat Religious Court is actually discussed. In this study, the authors use a qualitative method, namely research that uses words in their research, with the research subject being judges, and also employees of the Stabat Religious Court. From the research conducted, the researcher can conclude that the process of settling the husband's nusyuz case in the Stabat Religious Court generally begins with the wife suing her nusyuz husband, generally this lawsuit is called divorced. As for in the process, the judge will initially make peace efforts because the court adheres to the principle of making it difficult for divorce, if the mediation process is successful, a peace deed will be made. if it fails, the judge will continue the trial process with the agenda of reading the lawsuit, then answering, followed by answering, then proving to the conclusion. Then the judge will decide the matter in three forms, the first lawsuit is granted, the second lawsuit is rejected, or the third lawsuit is not accepted. If the outcome of the trial is a divorce then the court will issue a deed of divorce to both parties as the end of the process of resolving their case. Â